2001
DOI: 10.1152/jappl.2001.90.5.1714
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated muscle mechanoreflex control of reflex renal vasoconstriction in heart failure

Abstract: In heart failure (HF) patients, reflex renal vasoconstriction during exercise is exaggerated. We hypothesized that muscle mechanoreceptor control of renal vasoconstriction is exaggerated in HF. Nineteen HF patients and nineteen controls were enrolled in two exercise protocols: 1) low-level rhythmic handgrip (mechanoreceptors and central command) and 2) involuntary biceps contractions (mechanoreceptors). Renal cortical blood flow was measured by positron emission tomography, and renal cortical vascular resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
115
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 19 publications
6
115
1
Order By: Relevance
“…Similar findings have been reported in humans, as low levels of involuntary biceps contraction, a strategy used to selectively engage the mechanoreflex, has been shown to enhance renal vasoconstriction in CHF patients. 11 Taken together, these findings suggest that the EPR dysfunction observed in cardiomyopathy is mediated, in part, by the muscle mechanoreflex. The mechanisms by which the mechanoreflex causes augmentations in EPR function remain obscure.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Similar findings have been reported in humans, as low levels of involuntary biceps contraction, a strategy used to selectively engage the mechanoreflex, has been shown to enhance renal vasoconstriction in CHF patients. 11 Taken together, these findings suggest that the EPR dysfunction observed in cardiomyopathy is mediated, in part, by the muscle mechanoreflex. The mechanisms by which the mechanoreflex causes augmentations in EPR function remain obscure.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3][4][5][6] In addition, cardiovascular regulation during physical activity is clearly altered with CHF, because studies using dynamic and static forms of exercise have demonstrated augmentations in sympathetic nerve activity, vascular resistance, heart rate (HR), and blood pressure. [7][8][9][10][11][12][13][14][15] Two distinct neural control mechanisms are activated by exercise: central command and the exercise pressor reflex (EPR). Central command is a mechanism whereby signals from a central site responsible for recruiting motor units activate cardiovascular control areas in the brain stem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, sympathetic tone to muscle is elevated (24,29,36,42), renal vasoconstriction is enhanced (13,30,31,34), and the rise in muscle blood flow is attenuated in heart failure (13,25,35,41). The reduced blood supply to the kidney leads to excessive stimulation of renin secretion and inappropriate salt and water retention (6, 13), whereas the reduced skeletal muscle blood flow is an important contributor to exercise intolerance (51) in these patients.…”
mentioning
confidence: 99%
“…These observations suggest that the muscle metaboreflex is attenuated in HF. By contrast, the muscle mechanoreflex activation due to passive stretch of skeletal muscles evoked a significant elevation of muscle SNA 67) and enhanced renal vasoconstriction 68) in HF patients. These findings suggest that the muscle mechanoreflex is enhanced in HF.…”
Section: Contribution Of Rat Studies To Understanding Mechanisms Undementioning
confidence: 80%